PENGARUH MODEL PEMBELAJARAN PROJECT-BASED LEARNING DALAM MATA PELAJARAN KEWIRAUSAHAAN UNTUK MENINGKATKAN KREATIVITAS SISWA DI SMK KANSAI PEKANBARU - Ulima Tania; Nunuk Suryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the implementation of the Project-Based Learning (PJBL) model, to identify students' creativity levels before and after the implementation of PJBL, and to analyze the effect of PJBL on students' creativity in the Entrepreneurship subject at SMK Kansai Pekanbaru. A quantitative approach was used with a quasi-experimental method and a Nonequivalent Control Group Design, involving 22 students in the experimental class and 18 students in the control class. Data were collected using a 30-item creativity questionnaire and analyzed through descriptive statistics, normality and homogeneity tests, and an Independent Samples t-test using SPSS 26. PJBL was implemented through six stages: determining the essential question, designing the project plan, creating the schedule, monitoring the project, assessing the outcome, and evaluating the experience; students individually created promotional media using the Canva application. The results showed that the average creativity score of the experimental class increased from 123.32 (pretest) to 135.82 (posttest), a gain of 12.50 points, while the control class decreased from 122.50 to 120.00, a decline of 2.50 points. The Independent Samples t-test yielded t = 5.225 with a significance value of 0.000 < 0.05 and a Mean Difference of 15.000. Thus, H0 was rejected and Ha was accepted, indicating that the implementation of the Project-Based Learning model had a significant effect on students' creativity in the Entrepreneurship subject at SMK Kansai Pekanbaru.